Influence of Land Governance on Job Creation in Mindanao - Eleazar, Floradema C.; Ravanera, Roel; Gatus, Jose; Masangcay, Bonapart (World Bank, Washington, DC, 2017)
The World Bank is preparing a Mindanao Jobs Report (MJR) that aims jobs challenge and identify recommendations on how to create more and better jobs in the region. The MJR represents regional analysis of the Philippine development report (PDR) creating more and better jobs which identified key constraints and recommended an agenda for sustaining inclusive growth and addressing the jobs challenge. The study analysis of influence of land governance and employment creation in Mindanao aims to contribute to the analytical work that was carried out under the MJR through a more focused assessment of land governance in Mindanao.